CRITICAL DISCOURSE ANALYSIS OF HAILOTIM FACEBOOK PAGE AS AN INFORMATIONAL MEDIUM IN SOCIO-POLITICAL ISSUES AND LOCAL BUSINESS PROMOTION - Setiawan, Budi; Ramdan, Zamroni; Yusuf, Aiman Syahrizal; Deviyanto, Deviyanto; Agustina, Yulia (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This research aims at examining the HaiLotim Facebook page as a well-known source of informational media in the East Lombok area, especially in relation to social politics and support for local businesses. Data from 317 Hailotim Facebook page posts from May 2024 to June 2024 were collected and analyzed through the critical discourse analysis perspective of Norman Fairclough, which consists of three dimensions: text analysis, processing analysis, and social analysis. Research findings reveal the dual the role of HaiLotim Facebook page: first, as a discussion forum for local political movements, which is exemplified by posts that facilitate community dialogue regarding regional elections; and second, as a platform for local economic growth through the promotion of local business and tourist attractions. Since the page’s market target is based in East Lombok, the language employed in HaiLotim's posts is characterized by its casual, localized style, enhancing engagement and accessibility among its predominantly East Lombok audience. Nevertheless, the study acknowledges limitations regarding the generalization of the findings to other platforms and timeframe, as well as the need for wider investigation of social networking impacts and regional variations.